2010
DOI: 10.1302/0301-620x.92b3.22424
|View full text |Cite
|
Sign up to set email alerts
|

Timing of reconstruction of the anterior cruciate ligament in athletes and the incidence of secondary pathology within the knee

Abstract: We reviewed a single-surgeon series of 300 athletic patients who had undergone reconstruction of the anterior cruciate ligament in order to establish the relationship between the timing of the reconstruction and the incidence of meniscal and chondral pathology. The patients were divided into five groups according to the time from their injury to surgery as follows: less than two months, two to six months, six to 12 months, 12 to 18 months and more than 18 months. The presence of meniscal tears was recorded and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
89
1
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(100 citation statements)
references
References 22 publications
6
89
1
4
Order By: Relevance
“…Numerous studies have shown higher rates of medial meniscus tears, including ramp lesions, with increased delay before surgery. 3,[31][32][33][34][35] Furthermore, the rate of irreparable medial meniscus tears requiring meniscectomy may also be higher. 36 In our study, patients with PHMM lesions missed at first assessment had a significantly longer interval between injury and surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have shown higher rates of medial meniscus tears, including ramp lesions, with increased delay before surgery. 3,[31][32][33][34][35] Furthermore, the rate of irreparable medial meniscus tears requiring meniscectomy may also be higher. 36 In our study, patients with PHMM lesions missed at first assessment had a significantly longer interval between injury and surgery.…”
Section: Discussionmentioning
confidence: 99%
“…However, if the injury is treated conservatively, a higher incidence of medial meniscus tears occurs with the passage of time [ 83,114,142,146,154 ] . Smith and Barrett [ 146 ] reported in a study of 575 meniscus tears in ACL-de fi cient knees that the medial menisci tears were frequently peripheral and involved the posterior horn.…”
Section: Incidence Of Loss Of Meniscus Tissue With Acl Injuriesmentioning
confidence: 99%
“…Cipolla et al number of patients suffered medial meniscus tears. Kennedy et al [ 83 ] reported that patients had a signi fi cantly higher chance of sustaining a medial meniscus tear if 1 year had elapsed from their injury (odds ratio 7.99, P = 0.004). In their cohort of 300 athletic patients, a signi fi cantly higher incidence of degenerative changes were found in knees that were >6 months post-injury (odds ratio 4.04, P = 0.005).…”
Section: Incidence Of Loss Of Meniscus Tissue With Acl Injuriesmentioning
confidence: 99%
“…Despite this, to our knowledge, the best timing for hip arthroscopy has not yet been defined in the orthopaedic literature. As in the case of knee pathology [2], it appears that a general consensus has been reached by most surgeons that surgery should be deferred until the acute symptoms have resolved and conservative treatment has failed. Our aim was to correlate the results of hip arthroscopic surgery with the duration of a patient's preoperative symptoms.…”
Section: Introductionmentioning
confidence: 99%